A Multimodal Study on the Unique Sensing Behavior of a Guest@Metal‐Organic Framework Material for the Detection of Volatile Acetone. Issue 3 (1st December 2022) - Möslein, Annika F.; Gutiérrez, Mario; Titov, Kirill; Donà, Lorenzo; Civalleri, Bartolomeo; Frogley, Mark D.; Cinque, Gianfelice; Rudić, Svemir; Tan, Jin‐Chong
Abstract: Owing to their unique functionalities and tailorable properties that are unattainable in conventional materials, metal‐organic frameworks (MOFs) have emerged as candidate materials for next‐generation chemical sensors and optoelectronics. For instance, the ZnQ@OX‐1 composite material, comprising a light‐emitting guest encapsulated in the pores of the OX‐1 framework, affords excellent sensing performance: a visible color change upon exposure to volatile acetone. In this work, a multimodal study on the exceptional vapochromism of this composite material using high‐resolution spectroscopy techniques based on inelastic neutron scattering and synchrotron radiation is presented, supported by density functional theory calculations. While FTIR spectroscopy in the far‐IR and mid‐IR regions reveals the underlying interactions between ZnQ, OX‐1, and acetone, the limit of detection at 50 ppm is determined through in situ gas dosing experiments using fluorescence spectroscopy. In addition, in situ gas dosing on the single crystal level is achieved with near‐field infrared nanospectroscopy. Abstract : Upon exposure to volatile acetone, the luminescent ZnQ@OX‐1 composite material, comprising the guest molecule 8‐hydroxyquinoline zinc encapsulated in the metal‐organic framework OX‐1, visibly changes color. Using a suite of spectroscopic techniques, the underlying optical sensing mechanism is investigated. In situ gas dosing experiments reveal a limit of detection of 50 ppm, as well as gas adsorption on the single‐crystal level.